2007
DOI: 10.1016/j.maturitas.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms, hormone levels, and hot flashes in midlife women

Abstract: Objective-Hot flashes disrupt the lives of millions of women each year. Although hot flashes are a public health concern, little is known about risk factors that predispose women to hot flashes. Thus, the objective of this study was to examine whether sex steroid hormone levels and genetic polymorphisms in hormone biosynthesis and degradation enzymes are associated with the risk of hot flashes.Methods-In a cross-sectional study design, midlife women aged 45 to 54 years (n=639) were recruited from Baltimore and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 32 publications
1
42
2
4
Order By: Relevance
“…Similarly, Woods et al 51 reported that women with two CYP19 11r alleles had significantly more days of HFs during the middle and late menopausal transition and postmenopause than those with one or no allele. In contrast, Schilling et al 26 did not find any association between selected polymorphisms in the CYP19 or COMT genes and HFs. These differences in results might stem from differences in study design (e.g., the tested populations and analysis assumptions, such as including menopausal stage in the analysis).…”
Section: Genetic Polymorphismsmentioning
confidence: 82%
See 4 more Smart Citations
“…Similarly, Woods et al 51 reported that women with two CYP19 11r alleles had significantly more days of HFs during the middle and late menopausal transition and postmenopause than those with one or no allele. In contrast, Schilling et al 26 did not find any association between selected polymorphisms in the CYP19 or COMT genes and HFs. These differences in results might stem from differences in study design (e.g., the tested populations and analysis assumptions, such as including menopausal stage in the analysis).…”
Section: Genetic Polymorphismsmentioning
confidence: 82%
“…25 The association between HFs and lower levels of estradiol is fairly consistent. 3,13,[26][27][28] For example, Fentiman et al 28 showed, in a cross-sectional study, that a decrease in symptom severity was correlated with high estradiol levels. This finding was also observed in other cross-sectional, 26,27 1906 ZIV-GAL AND FLAWS review, 3 and longitudinal prospective 13 studies.…”
Section: Endocrinologymentioning
confidence: 99%
See 3 more Smart Citations